Motivation Differences behind Knowledge Sharing Behaviour among Instagram Food Bloggers in Bandung - Nurasiah, Sofa Parihah; Wisesa, Anggara (Jurnal Manajemen Teknologi, 2021)
Abstract. Since becoming a "pop culture" for the millennial generation in sharing information and knowledge, social media has been able to open opportunities for culinary industry players, especially restaurant owners and food bloggers, to collaborate using social media to achieve mutually beneficial goals. Food bloggers uniquely connect restaurants and consumers through culinary product reviews, categorised as knowledge sharing. However, the difference in the motivation behind the knowledge sharing process raises questions about the practice of knowledge sharing that is carried out because of monetary motivation and non-monetary motivation. Following that question, this study aims to understand the motivation behind knowledge sharing activity and sustainability carried out by food bloggers as knowledge contributors. Using the phenomenological approach and method, this research was conducted by arranging interviews with notable food blog account owners on Instagram to explore their experiences as a food blogger. The phenomenological analysis is used to reveal the essence of their experience related to motivation to become a food blogger that encourages them to share their knowledge on social media. The study conducted found that the shift from non-professionals to non-professional food bloggers was due to the trend of reviewing food and requests for cooperation from other Instagram users. On the go, no food blogger has purely monetary or non-monetary motivations. Both motivations emerge and have their respective impacts. Monetary motivation allows food bloggers to experience knowledge-sharing process and behaviour adjustments due to cooperation with restaurant owners. In contrast, non-monetary motivation enables food bloggers to carry out knowledge sharing processes and behaviours independently.Keywords: Knowledge sharing quality, monetary motivation, non-monetary motivation, food blogger, social media Abstrak. Sejak menjadi "pop culture" bagi generasi milenial dalam berbagi informasi dan pengetahuan, media social mampu membuka peluang bagi para pelaku industri kuliner khususnya pemilik restoran dan food blogger untuk berkolaborasi menggunakan media sosial guna mencapai tujuan yang saling menguntungkan. Food blogger secara unik menghubungkan restoran dan konsumen melalui review produk kuliner yang dapat dikategorikan sebagai knowledge sharing. Namun, adanya perbedaan motivasi di balik proses knowledge sharing kemudian menimbulkan pertanyaan mengenai kualitas knowledge sharing yang dilakukan karena motivasi moneter dan motivasi non-moneter. Menjawab pertanyaan itu, penelitian ini bertujuan untuk memahami motivasi di balik kegiatan berbagi pengetahuan       dan keberlanjutannya yang dilakukan oleh food blogger sebagai kontributor pengetahuan. Menggunakan pendekatan dan metode fenomenologi, penelitian ini dilakukan dengan melakukan wawancara kepada enam pemilik akun blog makanan ternama di Instagram untuk menggali pengalaman mereka menjadi food blogger. Analisis fenomenologis kemudian digunakan untuk mengungkap esensi dari pengalaman mereka terkait motivasi menjadi food blogger yang mendorong mereka untuk berbagi pengetahuan di dalam social media. Dari studi yang dilakukan, ditemukan bahwa pergeseran yang terjadi dari non-profesional menjadi non-profesional food bloggers terjadi karena adanya tren mengulas makanan dan permintaan kerjasama dari pihak lain pengguna Instagram. Pada perjalanannya, tidak ada blogger makanan yang murni memiliki motivasi moneter atau motivasi non-moneter. Kedua motivasi tersebut muncul dan memiliki dampak masing-masing. Motivasi moneter memungkinkan blogger makanan mengalami proses berbagi pengetahuan dan penyesuaian perilaku karena kerja sama dengan pemilik restoran, sedangkan motivasi non-moneter memungkinkan blogger makanan melakukan proses dan perilaku berbagi pengetahuan secara mandiri.Kata kunci: Kualitas berbagi pengetahuan, motivasi moneter, motivasi non-moneter, blogger makanan, media sosial